Socio-Demographic Determinants of Insurance Literacy among University Students in Indonesia - Siregar, Reza Yamora; Serpina, Nada (Journal of Indonesian Economy and Business, 2024)
Introduction/Main Objectives: This research aims to investigate the level of insurance literacy among economics and business students and identify the socio-demographic factors impacting the level of insurance literacy. Background Problems: Low insurance literacy has long been identified as the cause behind the weak insurance penetration growth in Indonesia. College students area potential market for the development and deepening of the insurance sector. Novelty: However, hardly any studies have been published that assess the insurance literacy of university students in Indonesia. This study also presents a unique view of students’ insurance knowledge across different universities in Indonesia, providing an understanding of the factors contributing to their literacy level. Research Methods: We conduct the commonly applied ordinary least squares test on the survey data collected using stratified random sampling. Findings/Results: The test results conclude that students from universities in Java, who have mothers who graduated from college, come from middle-income families, and live in Java have significantly higher insurance literacy levels compared to the rest of the students. However, gender and residency do not seem to significantly impact insurance literacy. Conclusion: Our study shows that socio-demographic factors influence university students’ level of insurance literacy. These findings provide valuable information for policymakers and insurance firms to target this potential market with their insurance products.